Remote conversations: The effects of mediating talk with technology - Sellen, Abigail (Human-Computer Interaction, 1995)
Three different video conferencing systems for supporting multiparty, remote conversations are described and evaluated experimentally. The three systems differed by how many participants were visible at once, their spatial arrangement, and control over who was seen. Conversations using these systems were compared to same-room (Experiment1) and audio-only (Experiment2) conversations. Specialized speech-tracking equipment recorded the on-off patterns of speech that allowed objective measurement of structural aspects of the conversations, such as turn length, pauses, and interruptions. Questionnaires and interviews also documented participants' opinions and perceptions in the various settings.